Studying the Effects of Thermal Neutrons Irradiation on CuInGaSe2 Thin Film - Murat Kaleli; Salman A. Ali; Murat Koç; Salih Akyürekli; Celal Alp Yavru (Journal of Madenat Alelem University College, 2020)
In this study, thermal evaporation method was used for coating CIGS thin film with about 1649 nm on a Mo layer of about 560.6 nm which in turn deposited by RF/DC sputtering method on a soda lime glass substrate. Then the samples were irradiated by an alpha neutron source 241AmBe for continuous five days irradiation to reach a neutron flux about 9×1010 n..cm-2.s-1 which is necessary to activate elements of the sample, then samples annealed at 200 ºC temperature in vacuum ambient at about 3×10-5 Torr. A structural, morphological and topographical analysis were conducted and accordingly the samples were characterized by means of XRD, SEM, EDS and AFM. As a result of thermal neutron irradiation, elemental constituent of CIGS slightly transmuted to new elements. Because of the impact energy of the neutrons the XRD peaks are changed and thin film surface average roughness factor increased to 7.97.